2015
DOI: 10.1016/j.jcin.2014.12.239
|View full text |Cite
|
Sign up to set email alerts
|

In-Stent Yellow Plaque at 1 Year After Implantation Is Associated With Future Event of Very Late Stent Failure

Abstract: In-stent atherosclerosis evaluated by yellow plaque at 1 year after the implantation of DES and the absence of statin therapy were risks of VLSF. The underlying mechanism of VLSF appeared to be the progression of atherosclerosis as demonstrated by the yellow plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…A recent prospective study has demonstrated that yellow plaque at the lesion previously treated with DES predicts future late stent failure. 20 Hypertension was negatively associated with thrombus, which was an unexpected finding, because most of the previous studies reported no association between hypertension and stent thrombosis. However, it is noteworthy that use of 1st-DES had the strongest association with thrombus.…”
Section: Discussionmentioning
confidence: 80%
“…A recent prospective study has demonstrated that yellow plaque at the lesion previously treated with DES predicts future late stent failure. 20 Hypertension was negatively associated with thrombus, which was an unexpected finding, because most of the previous studies reported no association between hypertension and stent thrombosis. However, it is noteworthy that use of 1st-DES had the strongest association with thrombus.…”
Section: Discussionmentioning
confidence: 80%
“…Yellow plaque, thrombosis and endothelial dysfunction are known to be particularly prevalent in the first generation DES, and such delayed arterial healing is considered to be associated with inflammation [21]. Furthermore, it has been reported that yellow plaque observed after DES placement is associated with subsequent cardiac events, and the underlying mechanism is presumed to be the development of arteriosclerosis [22].…”
Section: Yellow Plaque Thrombus and Erosion-like Intima (Eli)mentioning
confidence: 99%
“…9 A prospective study has shown that yellow plaque at the DES-implanted lesion predicts late stent-related events. 10 Thus, CAS has been used to compare vascular responses to different types of coronary stent. 11 Such ability to visualize plaque color is one of the greatest advantages of CAS over other intravascular imaging techniques.…”
Section: Editorialmentioning
confidence: 99%